Efektivitas Pemanggilan Surat Tercatat dalam Menciptakan Peradilan yang Sederhana, Cepat, dan Biaya Ringan: Pasca Peraturan Mahkamah Agung Nomor 7 Tahun 2022 - Dewantoro, Dewantoro (Universitas Proklamasi 45, 2023)
The summons for court summons and notification of court decisions to litigants keep up with the times by keeping up with developments in information and communication technology. The use of registered mail services replaces the role of the bailiff in summoning and notifying the decision. The hope for this change is to create justice that is simple, fast, and low-cost, but in the field, the role of registered mail services is not yet as expected.This research is normative juridical research to find research results that the use of registered mail services has not been effective in helping to create justice that is simple, fast, and low cost. The court needs to carry out socialization, and training in procedural law as well as monitoring and evaluation on cooperation in the use of mail services with PT Pos Indonesia (Persero). Administrative risks can be taken by the interested parties if errors in summons and notification of court decisions and decrees continue to be repeated.